Local Economic Development Strategy through MSMEs Empowerment: Case Study in Drenges Village - Suci, Siti Wahyu; Widiyanto, Widiyanto; Padmaningrum, Dwiningtyas (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyse the local economic development strategy through the empowerment of Balung Kuwuk MSMEs in Drenges Village. Methodology/approach: This study employed a qualitative descriptive method utilising a case study approach. Data collection techniques included observation, semi-structured interviews, and documentation. The analysis of data to determine the development strategy for Balung Kuwuk MSMEs was conducted using a SWOT analysis, combined with the Internal-External Matrix, to formulate context-specific empowerment strategies for rural MSMEs. Results/findings: The findings indicate that Balung Kuwuk MSMEs possess significant potential to drive the local economy in Drenges Village, supported by the abundant availability of cassava as the primary raw material. Nevertheless, community empowerment efforts to develop these MSMEs have not been effectively implemented, necessitating an aggressive strategy to strengthen and expand their capacity. Conclusion: Balung Kuwuk MSMEs can serve as a strategic driver of the local economy if supported by targeted, aggressive, and sustainable development strategies that fully empower MSME actors, strengthen institutional capacity, and optimise available local resources effectively Limitations: This case study has a narrow geographical scope, being limited to a single village, and therefore cannot be generalised to other rural or urban areas with different social, economic, cultural, and natural conditions and potentials. Contribution: This study provides input for government institutions and related agencies to support the development of Balung Kuwuk MSMEs in Drenges Village, aiming to improve human resource capacity and consistently enhance product quality.